THU0483 Characteristics of patients with active axial spondyloarthritis and comorbid fibromyalgia. differences according to fibromyalgia screening (first questionnaire) and fibromyalgia classification (ACR1990). (15th June 2017) - Perrot, S; Moltό, A; Etcheto, A; Boudersa, N; Claudepierre, P; Roux, N; Berenbaum, F; Martin, A; Sparsa, L; Coquerelle, P; Soubrier, M; Gossec, L; et al.
Abstract : Background: Fibromyalgia (FM) can be a comorbid condition in axial spondyloarthritis (axSpA). FM screening questionnaires and classification criteria fulfillment may demonstrate different prevalence and patients' characteristics may differ. Objectives: To evaluate frequency of comorbid FM, and the differences between axSpA patients with/without comorbid FM according to screening (FiRST) and classification tools (ACR1990 FM criteria). Methods: A multicenter national study involving 39 rheumatology centers in France included 519 patients with axSpA starting an anti-TNF treatment (PredictSpA study; ClinicalTrials.gov: NCT03039088 ). Patients (pts) were screened for FM with the FiRST questionnaire and classified as FM by ACR 1990 criteria. Demographic characteristics, comorbidities, axSpA characteristics, CRP and imaging were recorded in all patients. Kappa coefficient (and its 95% CI) was calculated to compare FiRST and ACR1990 criteria. Baseline characteristics associated with FM were evaluated by univariable and multivariable logistic regression (including the variables with a p value<0.20 in the univariable analysis). Results: In the 519 pts (females: 46%, age: 42±12 years, mean BASDAI 5.7±2.0, mean ASDAS-CRP 3.3±0.9), a comorbid FM was screened in 38% and diagnosed in 16% of pts. Agreement between FiRST and ACR1990 was poor, with a Kappa coefficient of 0.2 [0.2–0.3]. In the multivariable analysis, comorbid FM (by the FiRST questionnaire) in axSpA patients was independently associated with a lower education level, more sick leave, more heel pain, more frequent second line anti-TNF. Comorbid FM defined by the ACR1990 classification criteria was independently associated with heel pain and inversely associated with B27 haplotype. (Table) Conclusions: FM is frequently associated with active axSpA, with poor correlation between screening (FiRST) and diagnosis (ACR1990) test. Several characteristics are associated with comorbid FM, depending on FM classification and screening tools. References: Perrot S et al. Development and validation of the Fibromyalgia Rapid Screening Tool (FiRST). Pain. 2010;150:250–6. Acknowledgements: This study was conducted thanks to an unrestricted grant from MSD. Disclosure of Interest: None declared